Contraceptive technologies: Looking ahead to new approaches to increase options for family planning - Haddad, Lisa B. (Clin Obstet Gynecol, 2021)
With persistently high global rates of unintended pregnancy and contraceptive non-use, non-adherence and discontinuation, new contraceptive methods must address the needs of women and men who seek alternatives to their current options. Methods under development aim to reduce potential side effects, improve access and ease of use, ensure safety, increase secondary benefits associated with method use and expand options for both women and men. Developmental approaches employed to enhance current methods utilize new delivery systems and novel active pharmaceutical ingredients. This will improve overall user satisfaction with the methods used, while expanding the number of options available to provide choice and value user autonomy in the highly diverse contraceptive markets around the world..